Rapid detection of extended-spectrum-b-lactamase-producing Enterobacteriaceae in blood cultures using the ESBL NDP test in Cotonou, Benin - AFFOLABI, DISSOU (My University, 2017)
Purpose. Rapid and inexpensive tests for detecting extended-spectrum-b-lactamase (ESBL)-producing Enterobacteriaceae are needed, particularly in low-resource countries where infections with these bacteria constitute a major public health issue. The recently described ESBL NDP test performed well in developed countries. This study was designed to assess performance, cost and feasibility of this test in positive blood cultures, in Cotonou, Benin (West Africa). Methodology. The test was performed on 175 positive Bactec broth blood cultures containing Enterobacteriaceae, and blindly compared with the double-disc synergy test (DDST) for the phenotypic detection of ESBL producers. Results. There was a complete agreement between the ESBL NDP test and the DDST. On average, the time to give results was 37 min for a sample and the cost was US$ 7.3. Conclusion. The ESBL NDP test is rapid, relatively affordable and performed well in our setting.